The effect of inflation on growth: Evidence from a panel of transition countries - Max Gillman; Mark N. Harris (Cardiff University, Cardiff Business School, 2008)
The paper examines the effect of inflation on growth in transition countries. It presents panel data evidence for 13 transition countries over the 1990-2003 period; it uses a fixed effects, full-information maximum likelihood, panel approach to account for possible bias from correlations among the unobserved effects and the observed country heterogeniety. The results find a strong, robust, negative effect on growth, and one that declines in magnitude as the inflation rate increases. These results include a role for a normalized money demand, by itself and as part of a nonlinearity in the inflation-growth effect. And these results derive from both a baseline single equation model and one that is then expanded into a three equation simultaneous system. This allows for possible simultaneity bias in the baseline model.
Keywords: C23; E44; O16; O42; 330; growth; transition; panel data; inflation; money demand; endogeneity; Geldpolitik; Inflation; Wirtschaftswachstum; Panel; Transformationsstaaten